A new space approach on spacecraft flight software development using NASA cFS framework - Danilo José Franzim Miranda (2019)
This dissertation was motivated by a real-life problem of developing a Flight Software (FSW) for a commercial nanosatellite mission, heavily constrained in cost and schedule. FSW is a complex subject, demanding a software development team with competencies in embedded systems, real-time systems, spacecraft engineering and spacecraft operations in order to conceive a project. This set of skills is rarely found together, consisting of a great barrier for new entrants. The New Space FSW development approach proposed herein consists in four steps: 1) selection and adoption of a FSW framework; 2) compliance assessment of the framework with respect to applicable space software standards; 3) software design rules proposition to better adhere to framework and improve quality; 4) creation of a tool that facilitates the implementation of the aforementioned rules in the software development. NASA cFS was the chosen framework, being the central piece of this work. Despite its considerable heritage and success in several NASA scientific missions and being open source since 2015, cFS is still not widely adopted outside the American space agency. This work also helps filling the lack of academic literature with respect to frameworks employment and their systematic use in New Space missions.